Project management for dummies - Portny, Stanley E. (Stanley Erwin) (Hoboken, NJ : Wiley Pub., 2010)
This hands-on guide introduces you to the principles of project management and shows you how to put them to use so you can successfully manage a project from start to finish.
Includes index.
ARC
Keywords: Project management